Nucleation and Growth Synthesis of Siloxane Gels to Form Functional, Monodisperse, and Acoustically Programmable Particles1. (22nd May 2014) - Shields, C. Wyatt; Sun, Danping; Johnson, Kennita A.; Duval, Korine A.; Rodriguez, Aura V.; Gao, Lu; Dayton, Paul A.; López, Gabriel P.
Abstract Nucleation and growth methods offer scalable means of synthesizing colloidal particles with precisely specified size for applications in chemical research, industry, and medicine. These methods have been used to prepare a class of silicone gel particles that display a range of programmable properties and narrow size distributions. The acoustic contrast factor of these particles in water is estimated and can be tuned such that the particles undergo acoustophoresis to either the pressure nodes or antinodes of acoustic standing waves. These particles can be synthesized to display surface functional groups that can be covalently modified for a range of bioanalytical and acoustophoretic sorting applications.